Implementation of the Merdeka Belajar Kampus Merdeka (MBKM) Towards Policies at UIN Sunan Kalijaga Yogyakarta - Mubarok Fatahillah; Abd Razak Zakaria; Rika Evania Muslimatun (STAI Terpadu Yogyakarta, 2024)
The Merdeka Belajar Kampus Merdeka (MBKM) policy is a strategic initiative by Indonesia's Ministry of Education, Culture, Research, and Technology to create a more flexible, adaptive, and industry-relevant education system. This study explores the implementation of the MBKM policy at UIN Sunan Kalijaga Yogyakarta and its impact on students, faculty, and administrative staff. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation. The findings reveal that the MBKM implementation at UIN Sunan Kalijaga has led to significant changes in curriculum, teaching methods, and student engagement in off-campus activities. Additionally, the program encourages students to take a more active role in decision-making regarding their educational pathways, enhances curriculum relevance to industry needs, and strengthens students' skills to face workplace challenges. Overall, the MBKM policy at UIN Sunan Kalijaga positively impacts higher education quality by facilitating the development of skills that are more responsive to global changes.